Antimicrobial dressings: Comparison of the ability of a panel of dressings to prevent biofilm formation by key burn wound pathogens. Issue 8 (December 2015) - Halstead, Fenella D.; Rauf, Maryam; Bamford, Amy; Wearn, Christopher M.; Bishop, Jonathan R.B.; Burt, Rebecca; Fraise, Adam P.; Moiemen, Naiem S.; Oppenheim, Beryl A.; Webber, Mark A.
Highlights: The antibacterial activity of a range of antimicrobial dressings (AMDs) was tested. Large variability existed in the ability to prevent biofilm formation. Some AMDs were no better than non-AMDs in terms of antimicrobial impact. Acetic acid consistently prevented biofilm formation. Dressing choice should be guided by evidence-based assessment of efficacy. Abstract: Antimicrobial medicated dressings (AMD) are often used to reduce bacterial infection of burns and other wounds. However, there is limited literature regarding comparative efficacies to inform effective clinical decision making. Objectives: Following on from a previous study where we demonstrated good antibiofilm properties of acetic acid (AA), we assessed and compared the in vitro anti-biofilm activity of a range of AMDs and non-AMDs to AA. Methods: Laboratory experiments determined the ability of a range of eleven commercial AMD, two nAMD, and AA, to prevent the formation of biofilms of a panel of four isolates of Pseudomonas aeruginosa and Acinetobacter baumannii . Results: There is a large variation in ability of different dressings to inhibit biofilm formation, seen between dressings that contain the same, and those that contain other antimicrobial agents. The best performing AMD were Mepilex ® Ag and Acticoat. AA consistently prevented biofilm formation. Conclusions: Large variation exists in the ability of AMD to prevent biofilm formation and colonisation of wounds. A standardised in vitro methodology should be developed for external parties to examine and compare the efficacies of commercially available AMDs, along with robust clinical randomised controlled trials. This is essential for informed clinical decision-making and optimal patient management.